Chemical and nanoindentation study of diffusion during sintering of 12Ce-ZrO2/3Y-ZrO2 powder layers. Issue 2 (1st February 2018) - Roa, J.J.; Turon-Vinas, M.; Tovar, D.; Ledesma, J.; Anglada, M.
Abstract: Tetragonal zirconia polycrystals doped with 3% mol of yttria (3Y-ZrO2 ) exhibit excellent mechanical properties and biocompatibility. However, under humid environments, their surface structural integrity is degraded by aging (low temperature degradation). Co-doping with Ceria by starting from mixtures of 3Y-ZrO2 and 12Ce-ZrO2 powders can increase the resistance to low temperature degradation. In this study, systematic chemical and nanomechanical measurements have been conducted in powder multilayers of the12Ce-ZrO2 /3Y-ZrO2 system after sintering at different temperatures (from 1400 to 1600 °C) during 2 h in order to measure the distribution of diffusion of stabilizer solutes. The results indicate that the diffusion process zone at the 12Ce-ZrO2 /3Y-ZrO2 interface increases with sintering temperature by following an Arrhenius equation. Measuring the hardness by nanoindentation through the diffusion zone gives similar activation energy at high sintering temperatures. At low sintering temperatures, nanoindentation has not enough resolution at low sintering temperatures for the sintering time used.